CINdex: A Bioconductor Package for Analysis of Chromosome Instability in DNA Copy Number Data. (13th December 2017) - Song, Lei; Bhuvaneshwar, Krithika; Wang, Yue; Feng, Yuanjian; Shih, Ie-Ming; Madhavan, Subha; Gusev, Yuriy
The CINdex Bioconductor package addresses an important area of high-throughput genomic analysis. It calculates the chromosome instability (CIN) index, a novel measurement that quantitatively characterizes genome-wide copy number alterations (CNAs) as a measure of CIN. The advantage of this package is an ability to compare CIN index values between several groups for patients (case and control groups), which is a typical use case in translational research. The differentially changed cytobands or chromosomes can then be linked to genes located in the affected genomic regions, as well as pathways. This enables in-depth systems biology–based network analysis and assessment of the impact of CNA on various biological processes or clinical outcomes. This package was successfully applied to analysis of DNA copy number data in colorectal cancer as a part of multi-omics integrative study as well as for analysis of several other cancer types. The source code, along with an end-to-end tutorial, and example data are freely available in Bioconductor athttp://bioconductor.org/packages/CINdex/ .